Jesús Tepactepe: The rural subject and its non-peasant forms (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
The community of Jesús Tepactepec proposes a resignifi cation of its form of rural life, where work activities are mixed (agricultural and not peasant women) turning them into a multi-active population, which opens up doors to globalization, therefore to rural diversity from the process of historical pluriactivity within the community and the approach to the new rurality. Also, influence develops of income complementarity (variables/refuge) with (fi xed) wages in the reproduction of their rural culture. Of this how we advance with the analytical ethnography of everyday life pluriactive of rural households, transformed culture, rural subject (SR) today and its non-peasant forms. Of this The reader is invited to inquire into this research at Jesus Tepactepec.
Keywords: Culture; Globalization; Pluriactivity; New Rurality andRural Subject